Pressure as a limiting factor for life - Hazael, Rachael; Meersman, Filip; Ono, Fumihisa; McMillan, Paul F. (MDPI, 2016)
Facts concerning the stability and functioning of key biomolecular components suggest that cellular life should no longer be viable above a few thousand atmospheres (200–300 MPa). However, organisms are seen to survive in the laboratory to much higher pressures, extending into the GPa or even tens of GPa ranges. This is causing main questions to be posed concerning the survival mechanisms of simple to complex organisms. Understanding the ultimate pressure survival of organisms is critical for food sterilization and agricultural products conservation technologies. On Earth the deep biosphere is limited in its extent by geothermal gradients but if life forms exist in cooler habitats elsewhere then survival to greater depths must be considered. The extent of pressure resistance and survival appears to vary greatly with the timescale of the exposure. For example, shock experiments on nanosecond timescales reveal greatly enhanced survival rates extending to higher pressure. Some organisms could survive bolide impacts thus allowing successful transport between planetary bodies. We summarize some of the main questions raised by recent results and their implications for the survival of life under extreme compression conditions and its possible extent in the laboratory and throughout the universe.
Keywords: Extreme conditions; High pressure treatment; Food technology; Protein stability; Cell wall biochemistry; Bacterial survival; Interplanetary transport; Seeds; Spores; Artemia cysts